The Efficacy of Triptolide in Preventing Diabetic Kidney Diseases: A Systematic Review and Meta-Analysis - Liang, Dongning; Mai, Hanwen; Ruan, Fangyi; Fu, Haiyan (Frontiers in Pharmacology, 2021)
Ethnopharmacological Relevance: Triptolide (TP), the primary biologically active ingredient of Tripterygium wilfordii Hook F (TWHF), possesses the potential to solve the shortcomings of TWHF in treating diabetic kidney disease (DKD) in the clinic. Aim of the Study: We conducted a meta-analysis to evaluate the efficacy of TP in treating DKD and offer solid evidence for further clinical applications of TP. Materials and Methods: Eight databases (CNKI, VIP, CBM, WanFang, PubMed, Web of Science, EMBASE, and Cochrane library) were electronically searched for eligible studies until October 17, 2020. We selected animal experimental studies using TP versus renin–angiotensin system inhibitors or nonfunctional liquids to treat DKD by following the inclusion and exclusion criteria. Two researchers independently extracted data from the included studies and assessed the risk of bias with the Systematic Review Centre for Laboratory Animal Experimentation Risk of Bias tool. Fixed-effects meta-analyses, subgroup analyses, and meta-regression were conducted using RevMan 5.3 software. Inplasy registration number: INPLASY2020100042. Results: Twenty-six studies were included. Meta-analysis showed that TP significantly reduced albuminuria (14 studies; standardized mean difference SMD: −1.44 [−1.65, −1.23], I2 = 87%), urine albumin/urine creatinine ratio (UACR) (8 studies; SMD: –5.03 [–5.74, −4.33], I2 = 84%), total proteinuria (4 studies; SMD: –3.12 [–3.75, −2.49], I2 = 0%), serum creatinine (18 studies; SMD: –0.30 [–0.49, −0.12], I2 = 76%), and blood urea nitrogen (12 studies; SMD: –0.40 [–0.60, −0.20], I2 value = 55%) in DKD animals, compared to the vehicle control. However, on comparing TP to the renin–angiotensin system (RAS) inhibitors in DKD treatment, there was no marked difference in ameliorating albuminuria (3 studies; SMD: –0.35 [–0.72, 0.02], I2 = 41%), serum creatinine (3 studies; SMD: –0.07 [–0.62, 0.48], I2 = 10%), and blood urea nitrogen (2 studies; SMD: –0.35 [–0.97, 0.28], I2 = 0%). Of note, TP exhibited higher capacities in reducing UACR (2 studies; SMD: –0.66 [–1.31, −0.01], I2 = 0%) and total proteinuria (2 studies; SMD: –1.18 [–1.86, −2049], I2 = 0%). Meta-regression implicated that the efficacy of TP in reducing DKD albuminuria was associated with applied dosages. In addition, publication bias has not been detected on attenuating albuminuria between TP and RAS inhibitors after the diagnosis of DKD. Systematic Review Registration:https://clinicaltrials.gov/, identifier INPLASY2020100042